A physical unclonable function defined using power distribution system equivalent resistance variations - Helinski, Ryan; Acharyya, Dhruva; Plusquellic, Jim (2009 46th ACM/IEEE Design Automation Conference, 2009)
For hardware security applications, the availability of secret keys is a critical component for secure activation, IC authentication and for other important applications including encryption of communication channels and IP protection in FPGAs. The vulnerabilities of conventional keys derived from digital data can be mitigated if the keys are instead derived from the inherent statistical manufacturing variations of the IC. Robust silicon-derived keys are implemented using physically unclonable functions (PUFs). A PUF consists of a specialized hardware circuit and a mechanism to retrieve a set of responses under a variety of different challenges. In this paper, we propose a PUF that is based on the measured equivalent resistance variations in the power distribution system (PDS) of an IC. The effectiveness of the PUF is evaluated on twenty-four ICs fabricated in a 65 nm technology.